Śrī 5 Mahārājādhirāja Vīrendra Vīra Vikrama Sāha Devabāṭa baksekā ghoshaṇā, bhāshaṇa, ra sandeśaharū - Birendra Bir Bikram Shah Deva, King of Nepal, 1945- (Śrī 5 ko Sarakāra, Sañcāra Mantrālaya, Sūcana Vibhāga, 1972)
Royal proclamations, speeches, and messages.